A life cycle assessment of PCM and VIP in warm Mediterranean climates and their introduction as a strategy to promote energy savings and mitigate carbon emissions - Dimitra Papadaki; Spyros Foteinis; Vasileios Binas; Margarita N. Assimakopoulos; Theocharis Tsoutsos; George Kiriakidis (AIMS Materials Science, 2019)
The building stock in southern Europe grossly lacks sufficient thermal envelope insulation, leading to high energy inputs and corresponding CO2 emissions. Phase change materials (PCMs) and vacuum insulations panels (VIPs) could be an innovative way to curtail the high heating and cooling energy inputs to maintain comfort; however, their efficiency and environmental performance in the southern Mediterranean climate is largely unknown. To this end, two demo houses, 27 m3 each, were constructed in the island of Crete, southern Greece. The first was constructed using conventional building materials, while in the second PCMs and VIPs were used, as a research test-bed. Actual life cycle inventory (LCI) data were collected and the life cycle assessment (LCA) methodology was employed to estimate the environmental impacts attributed both to their construction and operational phase. Compared to the conventional demo house the one covered with PCMs and VIPs appear to have a 34% higher total environmental footprint, which is attributed to the production process of PCMs and VIPs. Nonetheless, the energy savings observed during the operational phase, attributed to their higher thermal insulation, can compensate the higher environmental footprint of the construction phase within a year, depending on PCM’s enthalpy. Specifically, it was identified that PCMs and VIPs largely reduced daily indoor temperature fluctuations, improving indoor thermal comfort and leading to energy savings. As such, even though their installation is associated with an initial higher environmental footprint, large energy savings, compared to conventional demo house, are achieved during its operational phase. This suggests that the introduction of PCMs and VIPs could be an efficient and environmentally friendly route to enhance energy savings and reduce the environmental footprint of building stock.